Indigenous agriculture at the beginning of the twenty-first century: the Guaraní Mbyás minority conserves ethnoknowledge and agrobiodiversity within the remnants of the Brazilian Atlantic Forest - Fernandes, Lucas Mazzero (2022)
Swidden agricultural practices reflect a great deal of Indigenous and traditional ethnobotanical knowledge; however, such system and livelihoods are in decline worldwide and tend to disappear. This study aimed to survey the main characteristics of land use and agrobiodiversity of the swidden culture practiced by the Guaraní, in Serra do Mar (São Paulo state, Southeast Brazil). We likewise studied the socioeconomic and cultural characteristics of the Guaraní, focusing specifically on their ethnobotanical knowledge, to help conserve traditional agricultural practices in the deep tropics. A total of eighteen ethnobotanical surveys were carried out on 18 production units (10 × 10 m) in the cultivation phase after combustion took place. All species of agricultural use were indicated by the smallholders and identified to species level. Semi-structured interviews based on the design and diagnosis method World Agroforestry Centre (ICRAF) were carried out in either Portuguese or the native language with 48 smallholders in the village. Main topics discussed were the history of each sampled plot, socio-economic aspects of the production units, aspects of agricultural management to characterize the level of intensification, and forms of managing vegetation and criteria for making decisions about the maintenance of wild species in the agricultural plots. The ethnobotanical survey showed 65 varieties of plants for agricultural use, totaling 39 species, they are used for cultural-ritualistic, ecological, food, economic, medicinal, and ornamental aspects. Main crops found were corn (Zea mays), potato (Solanum tuberosum) and peanut (Arachis hypogaea). Fire is vital for Guarani’s agricultural practices. Fields are small and occupy just 0.25% of the indigenous land. The Guaraní’s traditional agroforest systems are independent of external inputs and are important for conservation of seeds and agrobiodiversity. There are three factors that maintain the dynamics of Guarani’s agricultural systems, namely: religiosity, the network of kinships and the existence of legal owned territories. Swidden and slash and mulch systems are part of the maintenance of the cultural autonomy of the Guaraní, providing them with a way to obtain financial and food resources directly and indirectly from the biome in a sustainable way. Hence, protecting this ethnoecology guarantees the cultural, physical, and social existence of the Guaraní and likewise helps to conserve the remnants of the Atlantic Forest hotspot.